Incidencia de la actividad física en el entorno familiar durante el confinamiento por COVID – 19 - Andrés José, Castro Molina (2021)
ABSTRACT The present research project titled, Incidence of physical activity in the family environment during confinement by COVID - 19, was carried out an explanatory bibliographic review study. In this research project, we have analyzed how physical activity affects the family environment since due to the confinement that the country and the world is going through due to COVID - 19, a virus originated in 2019 in the city of Wuhan in China. The whole family has suffered from many diseases such as stress, obesity, anxiety and depression, for this reason it is said that in order to keep the mind occupied, it is necessary to carry out activities with a common purpose and that better physical activity since from the smallest to the elderly. They have to maintain the active body and the mobility of the joints. In the bibliographic review has obtained that doing physical activity there are many more benefits, whether social, psychological, emotional and many more. In the family environment has said that communication is not much since the age difference the activities are very different, doing physical activity with all family members is favorable for harmonious coexistence. According to some studies carried out, it is said that physical activity in the family also helps the academic performance of children because parents occupy a very important place in the development of their children. The World Health Organization carried out a program that helps all members of the family to exercise physical activity in loads differentiated by age. In the bibliographic review, it was obtained that communication between family members is much better with the practice of physical activity. Key Words. Confinement, physical activity, family environment, COVID - 19. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258